Assessing people with dementia participating in cognitive stimulation activities—A qualitative pilot video analysis exploring the importance of facilitating the participation. (11th June 2021) - Thoft, Diana Schack; Ottesen, Anna Camilla; Jensen, Anne Melchior; Ward, Alison
Abstract: Background: This pilot video analysis was part of a feasibility control study, which aimed to gain information about the size and variability of the changes in outcome measures to plan a substantive effect study. It compared a cognitive stimulation programme named Lifelong Learning with other existing dementia services. Objective: The pilot video analysis explored how facilitation is performed, when assessing people with dementia with standardized measures, to ensure their participation in research. Design: A test battery of five measures (Mini‐Mental State Examination (MMSE), Quality of Life in Alzheimer's Disease Scale (QoL‐AD), General Self‐Efficacy Scale, Rosenberg Self‐Esteem Scale and Hawthorn Friendship Scale) was used. Each assessment was video‐recorded. The findings from a microanalysis of 10 videos are presented in this article. Setting: The study involved 55 active participants with mild‐to‐moderate dementia in six municipalities in Northern Denmark. Results: The identified themes related to supportive facilitation: Positive facilitator strategies; Creating a safe and comfortable environment ; and to dilemmas in facilitation: Balancing multiple dilemmas and Balancing the MMSE test . Discussion: Results are discussed in relation to using standardized measures. Conclusion: The quality of facilitation when using standardized measures is of great importance as it may influence the participant, the assessment and the answers given. The facilitation role needs to be thoroughly planned and executed with ethical consideration to improve the participation of vulnerable groups in research and ensure a person‐centred approach. Patient or public contribution: The identified measures were chosen based upon previous qualitative results and user‐involvement workshops with people with dementia.